Gender, Risk and Journalism. (2nd October 2016) - Harris, Janet; Mosdell, Nick; Griffiths, James
Abstract : The central concern of this paper is to address the question, "Is it more dangerous to be a woman journalist when reporting conflict". Beck states "risk is the anticipation of the catastrophe—so it is existent and non-existent". Is the contention that female journalists are more at risk, knowledge, or a construction of knowledge? Are editors and journalists who decide that women are more at risk merely anticipating a catastrophe? There is no certainty, of course, that women are more at risk, but the fear that they might be can prevent them from being sent to cover conflict, or force them to decide not to go to dangerous places. Certainly, an improvised explosive device or rocket fire does not distinguish between sexes. In many situations being female actually helps women journalist in conflict zones. In this paper we present findings from a survey of journalists who work in conflict zones and ask whether it is the job or the gender which is the most dangerous?